2017
DOI: 10.1136/bcr-2017-222179
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic meningioma: a rare cause of mediastinal lymphadenopathy.

Abstract: DescriptionA 69-year-old man with known, stable atypical meningioma of the brain diagnosed 5 years previously presented with severe shortness of breath. The patient had previously been treated with surgery and radiotherapy to the brain. Chest X-ray revealed bulky mediastinal lymphadenopathy (figure 1). CT (figure 2) confirmed mediastinal and upper abdominal lymphadenopathy in addition to multiple pulmonary emboli. The patient underwent an endoscopic ultrasound and fine-needle aspiration (EUS-FNA), an establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Metastasis to the mediastinal lymph nodes is usually found concurrently with pulmonary metastasis. Mediastinal lymph node metastasis from a meningioma without pulmonary metastasis is very rare; we found only two cases while searching Medline 4,5 . One case involved a mediastinal metastasis from an intracranial meningioma, similar to the case presented here, while the second case involved metastasis from an intramedullary spinal meningioma of the thoracic vertebra.…”
Section: Discussionsupporting
confidence: 71%
“…Metastasis to the mediastinal lymph nodes is usually found concurrently with pulmonary metastasis. Mediastinal lymph node metastasis from a meningioma without pulmonary metastasis is very rare; we found only two cases while searching Medline 4,5 . One case involved a mediastinal metastasis from an intracranial meningioma, similar to the case presented here, while the second case involved metastasis from an intramedullary spinal meningioma of the thoracic vertebra.…”
Section: Discussionsupporting
confidence: 71%
“…Nevertheless, they were rarely reported with aggressive behavior and metastasis to regional or distant organs in various case reports. [4][5][6][7][8][9][10] Meningiomas with aggressive behavior would either directly invade the surrounding tissue, or disseminate mostly via hematogenous route, and less frequently via lymphatic and cerebrospinal fluid (CSF) pathways. [10][11][12][13] Intracranial meningiomas are expected for local invasion involving intracranial venous channels, bones, soft tissue and paranasal sinuses, in contrast to distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…10 Moreover, liver, lymph nodes, bones, peritoneum, scalp and orbita were reported for being metastasized by meningiomas. [4][5][6][7][8][9] Despite of case reports, the risk factors and metastasis pattern are quite unknown for intracranial meningiomas. Surov et al reviewed the reports of 115 cases with metastatic meningiomas and found that the most frequent metastasized meningiomas were WHO grade III (40%), followed by grade I (33.9%), and grade II (20.9%) meningiomas.…”
Section: Discussionmentioning
confidence: 99%